Genetic variability and correlation studies among different Lilium genotypes - KUMARI, SANGEETA; DHIMAN, S R; DHIMAN, M R; SHARMA, PUJA; DOGRA, R K (The Indian Journal of Agricultural Sciences, 2020)
The present study was carried out for two years (2016-18) to estimate the genetic variability, heritability, genetic advance, genetic gain and correlation among 18 Lilium genotypes. Findings revealed characters such as number of bulblet/plant, number of leaves/plant and number of flowers/plant recorded high genotypic coefficient of variability (GCV). High heritability coupled with moderate genetic advance recorded for number of leaves/plant, plant height and stem length. Moderate heritability with highest genetic gain recorded for number of bulblets/plant followed by traits such as number of leaves per plant, leaf width, number of flowers/plant and weight of bulblet etc. Significant positive correlation of yield parameter (number of flowers per plant) recorded with plant height, number of leaves per plant, leaf length, stem length, stem diameter, duration of flowering, bulb diameter and weight of bulb etc. Maximum positive direct effect of days to flower bud formation, number of leaves per plant, bulb diameter, weight of bulb, leaf length, stem length etc. on number of flowers per plant revealed the true relationship between them and selection on the basis of these characters would be more effective for the improvement among Lilium genotypes.